2002
DOI: 10.1109/tvt.2002.801739
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive QoS for wireless multimedia networks using power control and smart antennas

Abstract: Abstract-This paper addresses the problem of adaptive quality-of-service (QoS) for mobile multimedia services under a power controlled wireless network using smart antennas. Given the nature of multimedia, we chose the signal-to-interference and noise ratio (SINR) of each user's channel as the QoS index. We direct our attention toward two problems. The first is to increase the SINR levels for multimedia users as much as the system can provide for, under the channel fading and interference conditions. Different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
0
7
0
2
Order By: Relevance
“…Several works have analyzed the influence of the spectral radius in different optimization problems. For example, reference [6] evaluates the gradient of the spectral radius in order to modify its value. In [7], a geometrical interpretation of the feasibility of the power minimization problem is provided for the uplink of a 2-users single-cell system.…”
Section: Improving the Feasibility Of Jpcob-sdlmentioning
confidence: 99%
“…Several works have analyzed the influence of the spectral radius in different optimization problems. For example, reference [6] evaluates the gradient of the spectral radius in order to modify its value. In [7], a geometrical interpretation of the feasibility of the power minimization problem is provided for the uplink of a 2-users single-cell system.…”
Section: Improving the Feasibility Of Jpcob-sdlmentioning
confidence: 99%
“…In [9], the authors combined SPC with the active link protection (ALP) scheme to maintain a minimum transmission rate for each user while minimizing the number of rate changes by smoothing the realized SIR s. A problem of how to control the transmission rates for maximizing system throughput while simultaneously minimizing the transmission powers was studied in [10]. In [11], the authors proposed adaptive QoS for wireless multimedia networks using power control and smart antennas. They showed that this method significantly increases the average SIR levels for multimedia users.…”
Section: Introductionmentioning
confidence: 99%
“…Quality of Service (QoS) is vital when streaming video over wireless networks [1][2] [3]. In this paper we present a practical implementation of an advanced and robust wireless audiovisual system.…”
Section: Introductionmentioning
confidence: 99%